2012
DOI: 10.1007/s00430-012-0247-0
|View full text |Cite
|
Sign up to set email alerts
|

Herpes simplex virus type 1 induces simultaneous activation of Toll-like receptors 2 and 4 and expression of the endogenous ligand serum amyloid A in astrocytes

Abstract: Herpes simplex virus type 1 (HSV-1) is the most common pathogenic cause of sporadic acute encephalitis and it produces latent persistent infection lifelong in infected individuals. Brain inflammation is associated with activation of glial cells, which can detect pathogen-associated molecular patterns (PAMPs) through a variety of pattern-recognition receptors (PRR), including Toll-like receptors (TLRs). In this study, we evaluated the expression and activation of TLR2, TLR3, and TLR4 in HSV-1-infected astrocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 40 publications
2
36
0
Order By: Relevance
“…Although the functions of Gbp4 and Gbp8 in T. gondii infection are not understood, these molecules might be associated with IFN-␥-dependent host defense. Furthermore, previous research has shown that CXCL9/MIG, CXCL10/IP-10, and CCL5/RANTES are chemokines predominantly induced in the brains of BALB/c mice during chronic infection with T. gondii (27).…”
Section: Discussionmentioning
confidence: 93%
“…Although the functions of Gbp4 and Gbp8 in T. gondii infection are not understood, these molecules might be associated with IFN-␥-dependent host defense. Furthermore, previous research has shown that CXCL9/MIG, CXCL10/IP-10, and CCL5/RANTES are chemokines predominantly induced in the brains of BALB/c mice during chronic infection with T. gondii (27).…”
Section: Discussionmentioning
confidence: 93%
“…In macrophages, TLR-2 promotes autophagy (Chuang et al, 2013), and intracranial HSV-1 infection stimulates TLR-2-dependent expression of the inflammatory cytokines IL-1b, IL-6 and TNF-a by microglia, astrocytes, neutrophils and monocytes (Aravalli et al, 2005;Villalba et al, 2012;Wang et al, 2012). However, in both macrophages and human foreskin fibroblasts, HSV-1 actually inhibits the secretion of mature IL-1b, apparently related to the trapping of caspase-1 by actin clusters (Johnson et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…TLR-2 induces inflammatory cytokine production by microglia, astrocytes, neutrophils and monocytes following HSV-1 intracranial infection (Aravalli et al, 2005;Villalba et al, 2012;Wang et al, 2012), but its induction in melanoma cells, in the context of oncolysis, and as related to direct cytokine secretion, is unknown. As autophagy was previously linked to cytokine secretion (Crişan et al, 2011;Harris, 2011), A2058 and A375 cells were mock-infected with PBS or infected with D PK (m.o.i.…”
Section: Inflammatory Cytokines Are Upregulated Through Autophagy-depmentioning
confidence: 99%
“…Brain inflammation due to infection is associated with the activation of the local innate immune system. This could be a crucial mechanism leading to the neuronal damage, as it was also described in the case of HSK, where a chronic inflammatory reaction in response to viral reactivation in the eye may lead to vision impairment and even blindness [810, 23]. …”
Section: Discussionmentioning
confidence: 99%